Assessment of central and peripheral accommodative lag by aberrometry - Sapkota, Kishor (2022)
Accommodation lag is important factor for normal vision. Higher lag of accommodation may cause various ocular symptoms particularly during near tasks. In this study, the lag of accommodation was assessed in the peripheral retina and it was compared with the central accommodative lag with aberrometer. In this cross-sectional study, fifty-three young subjects with normal visual acuity and without any active ocular disease or past ocular surgery were included. Aberrations in the central and peripheral field of view up to 30° off axis from the centre in horizontal and vertical meridian in 10° steps were measured with Hartmann-Shack aberrometer with stimulation of accommodation by -2.50D lens. Accommodative stimulus and accommodative response were calculated with defocus and hence accommodative lag was obtained. Accommodative lag in the centre and periphery was compared. Repeated measure of ANOVA showed that there were significant differences in lag of accommodation in various eccentricities (F(8.912, 454.514) = 2.372, p = 0.013). Pairwise test showed that lag in the centre was similar with lag on other peripheral field of view (p > 0.05). However, accommodative lag at 10° nasal field was significantly lower than the lag at 20° temporal, 20° nasal, 30° temporaland 30° nasal (p < 0.05). Similarly, lag at 10° superior fixation was lower than lag at 20° temporal, 20° nasal, 30° temporal and 30° nasal fixations (p < 0.05). We found higher lag of accommodation in horizontal off-axis fixations in comparison to that of vertical off-axis fixations (p < 0.05). Lag of accommodation was positive correlated with vertical coma and primary spherical aberrations but negative correlated with secondary spherical aberrations (p < 0.05). Thus, Hartmann-Shack aberrometer was successfully used to assess accommodative lag in the peripheral field of view up to 60° visual field. Peripheral lag of accommodation depends up on eccentricity. Lag was found higher in horizontal off-axis fixation than at vertical fixations. Coma and spherical aberration had association with lag.